Triton's Variable Interaction With Neptune's Magnetospheric Plasma. Issue 11 (9th November 2021) - Liuzzo, Lucas; Paty, Carol; Cochrane, Corey; Nordheim, Tom; Luspay‐Kuti, Adrienn; Castillo‐Rogez, Julie; Mandt, Kathleen; Mitchell, Karl L.; Holmström, Mats; Addison, Peter; Simon, Sven; Poppe, Andrew R.; et al.
Abstract: The tilt between Neptune's magnetic and rotational axes, along with Triton's orbital obliquity, causes a strong time variability of the moon's local electromagnetic environment. To constrain Triton's interaction with the ambient magnetospheric plasma, we apply a hybrid (kinetic ions, fluid electrons) model including the moon's ionosphere and induced field. To represent the extremes in the changes to the local electromagnetic field over a synodic rotation, we consider two orientations between the ambient magnetic field and flow velocity. For each, we first investigate the (analytical) magnetic signatures associated with the superposition of Triton's induced field and the magnetospheric field in the absence of any plasma interaction effects. To constrain the effect of Triton's ionosphere on the currents, we model the interaction between the ionospheric and magnetospheric plasma in isolation from the moon's inductive response, before combining these effects to investigate the complex scenario of plasma interaction and induction. Finally, we explore the sensitivity of the plasma interaction to changes in the ambient plasma density and the strength of Triton's inductive response. Despite plasma interaction signatures that dominate the plasma perturbations far from the moon (beyond ∼ 3 Triton radii), we illustrate that the induced field is clearly discernible within ∼ 3 Triton radii, regardless of the moon's location within Neptune's magnetosphere. We find that the orientation of the magnetospheric field and velocity vectors strongly affects Triton's plasma interaction; at times, resembling those of Jupiter's or Saturn's moons, while at others, revealing unprecedented signatures that are likely unique to moons of the ice giants. Key Points: We constrain the time variability in signatures associated with plasma interaction and induction at Triton, Neptune's largest moon Despite the presence of plasma currents far from the moon, Triton's induced field dominates the near‐surface magnetic field perturbations The tilt of Neptune's magnetic and rotation axes generates a plasma wake that is strongly displaced out of Triton's geometric plasma shadow